Stress as worsening of the signs and symptoms of the geographic tongue during the COVID-19 pandemic: a pilot study - Miriam Beatriz Jordão Moreira Sarruf; Valquiria Quinelato; Guilherme Jordão Moreira Sarruf; Henrique Eduardo Oliveira; Jose Albuquerque Calasans-Maia; Hilka Quinelato; Telma Aguiar; Priscila Ladeira Casado; Larissa Maria Assad Cavalcante (BMC Oral Health, 2022)
Abstract Background Geographic Tongue (GT) is a benign inflammatory disorder of unknown etiology, which is characterized by the loss of epithelium due to the atrophy of filiform papillae. It usually occurs on the dorsum of the tongue and may extend to its lateral edges. It appears as an erythematous area surrounded by whitish and slightly elevated margins. In most cases, the condition is asymptomatic, although some individuals may report symptoms that include a burning sensation of the tongue. Objective Assess whether there was a change in the clinical aspect of Geographic Tongue (GT) during the COVID-19 pandemic. Methods Thirty-two participants were recruited from Dentistry School Universidade Federal Fluminense. Anamnesis and oral examination were performed to collect medical history. The participants were split into two groups: control group (no GT) n = 20 and test group (with GT) n = 12. In the second step, nine participants from a 12 (75%) of the test group were contacted by phone and answered a questionnaire about changes in the signs and symptoms of GT during the pandemic. The subjects were subdivided into two groups: GT with and without signs and symptoms exacerbation. Results In the first phase of the research, no statistical difference between control and test groups was observed regarding clinical criteria such as age (p + 0.72), gender (p = 0.24), and systemic diseases (p = 0.58). In the second phase, there was a statistical difference between GT groups with or without symptom exacerbation in terms of age and stress as a factor of the oral symptoms (p = 0.3 and 0.2), respectively. Younger patients showed a worsening of the oral lesions related to GT (p = 0.3) and reported stress during the pandemic (p = 0.02). Conclusion Younger patients were more susceptible to stress and presented more exacerbation of the oral lesions related to GT.